AB0298 High level of anti-ccp antibodies is predictive of good response to rituximab in patients with active rheumatoid arthritis. (23rd January 2014) - Gardette, A.; Ottaviani, S.; Tubach, F.; Nicaise-Roland, P.; Palazzo, E.; Gill, G.; Meyer, O.; Dieudé, P.
Abstract : Background: In the current era, where the number of new biologic targets and related therapies for rheumatoid arthritis (RA) is rapidly increasing, identification of factors that predicts the response to biologic therapies is a key issue. Previous studies reported that an anti-CCP positive status is predictive of a good response to Rituximab (RTX) in RA. A quantitative approach could be a good way to better detect subset of individuals that are more likely responders. Objectives: We investigated whether anti-CCP serum levels were predictive of the response to RTX at M6 in patients having active RA. Methods: 114 RA patients treated with RTX were retrospectively included. The primary criterion was the decrease of DAS28 >1.2 at M6. Secondary efficacy criteria included the variation of DAS28 (ΔDAS), SJC, TJC, VAS pain, ESR, CRP and use of corticosteroids. Independent predictors of good response were investigated by using multivariate logistic regression analysis. Results: A total of 114 RA patients (81.6% of female, mean age 53.3 +/- 11.9 years and mean disease duration: 10.9 +/- 8.3 years, 75.2% RF+) were included. Anti-CCP antibodies were present in 81.6% of patients with a median level of 583 [195-1509] U/ml. A decrease of DAS28 >1.2 was observed in 38.6% of patients. In univariate analysis, high anti-CCP level was an independent factor associated with a response to RTX (median 1122 [355-1755] vs. 386 [143-800] U/ml, P =0.0059) at M6. Using the cut-off level of 1000 U/ml, multivariate logistic regression analysis, identified CCP+ patients with anti-CCP levels >1000 U/ml were 5 times more likely to achieve the decrease of DAS28 >1.2 ([OR: 5.10; 95% CI: 1.97-13.2], P =0.0008). High anti-CCP level was also predictive of a higher decrease of i) the DAS28 ( P =0.0371) ii) TJC ( P =0.0469), at M6. Conclusions: High anti-CCP level is an independent predictive factor of response to RTX at M6 in RA patients. This factor is easily assessed in clinical practice, can help to a personalised medicine and to select the best candidates for RTX treatment. Disclosure of Interest: None Declared